Relationship between faculty characteristics and their entrepreneurial orientation in higher education institutions in Kuwait - Oualid Abidi; Khalil Nimer; Ahmed Bani-Mustafa; Sam Toglaw (Journal of Innovation and Entrepreneurship, 2022)
Considering intrapreneurship theory, this study aims to examine the extent to which the entrepreneurial orientation of faculty employed at Kuwaiti higher education institutions differ across their individual-level attributes. Faculty entrepreneurial orientation will be assessed at three levels, i.e., innovativeness, risk-taking, and proactivity. For this purpose, we surveyed a sample of 291 faculty from Kuwaiti colleges and universities. The core constructs were operationalized using scales validated in previous studies. The hypothesized relationships were tested using the structural equation modeling method. Our findings indicate that while female faculty are more proactive than men, males are innovative and risk-takers to some extent. Moreover, Ph.D. holders are more proactive and innovative than Master's degree holders. The relationship between specialization and both innovativeness and risk-taking is significant only for business, but not for engineering. Teaching experience is more positively correlated with faculty proactivity. The number of scientific publications is negatively associated with faculty risk-taking propensity. Additionally, faculty who cumulated significant industry experience are proactive in identifying long-term opportunities and threats for their institutions. Having earned professional certifications is positively related to some aspects of innovativeness and proactivity. Finally, faculty who received their latest degree from a non-accredited institution are more active in realizing ideas at work.
Keywords: 650; Entrepreneurial orientation; Experience; Gender; Higher education institutions; Qualifications; Scientific productivity